The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10620-015-3772-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Hepatitis B Virus Infection with Nonalcoholic Fatty Liver Disease: Possible Mechanisms and Clinical Impact

Abstract: Hepatitis B virus (HBV) infection is a major etiology of chronic liver disease worldwide. In the past decade, nonalcoholic fatty liver disease (NAFLD) has emerged as a common liver disorder in general population. Accordingly, the patient number of chronic hepatitis B (CHB) concomitant with NAFLD grows rapidly. The present article reviewed the recent studies aiming to explore the relationship between CHB and NAFLD from different aspects, including the relevant pathogenesis of CHB and NAFLD, the intracellular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 119 publications
(158 reference statements)
3
36
2
Order By: Relevance
“…In the present large‐scale cohort study of apparently healthy individuals, we demonstrated a longitudinal association between HBsAg positivity and the development of dyslipidaemia over time. HBV carriers may be more likely to have a healthy lifestyle favourably affecting cholesterol levels compared to non‐carriers . However, in our study, the inverse association of HBsAg positivity with lipid parameters including total cholesterol, LDL‐C, triglycerides, non‐HDL cholesterol, apoA1 and apoB persisted after adjusting for possible confounders including smoking, alcohol intake, exercise, and BMI.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In the present large‐scale cohort study of apparently healthy individuals, we demonstrated a longitudinal association between HBsAg positivity and the development of dyslipidaemia over time. HBV carriers may be more likely to have a healthy lifestyle favourably affecting cholesterol levels compared to non‐carriers . However, in our study, the inverse association of HBsAg positivity with lipid parameters including total cholesterol, LDL‐C, triglycerides, non‐HDL cholesterol, apoA1 and apoB persisted after adjusting for possible confounders including smoking, alcohol intake, exercise, and BMI.…”
Section: Discussioncontrasting
confidence: 68%
“…Fourth, differences between HBsAg‐positive and ‐negative subjects may exist in lifestyle, including smoking, alcohol use, physical activity and diet. Previous studies reported that HBV‐infected patients are more likely to have healthy life habits and to avoid risk factors that could contribute to adverse health outcomes . In order to control for potential confounding variables including smoking, alcohol use and physical activity, we adjusted for those confounders in our model and found an independent association between hepatitis B infection and a lower risk of incident dyslipidaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Due to increase in consumption of fat-rich diet coupled with sedentary lifestyle, the incidence of NAFLD is increasing [8]. Thus, the frequency of patients with CHB and concomitant NAFLD is also increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Early stage of NAFLD is defined as the presence of steatosis in more than 5% of hepatocytes [8]. HBV X protein is reported to induce hepatic steatosis by enhancing the expression of liver fatty acid binding proteins [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation